1992
DOI: 10.1142/s0129055x92000066
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Waves and Causality

Abstract: A strictly ordered hierarchy of eight causal properties encountered in General Relativity is reviewed for the explicit case of the gravitational plane waves. Illustrative proofs are given to the effect that the place of these space-times is precisely known in the hierarchy: they are causally continuous, but not causally simple. The other conditions of the hierarchy are also discussed separately, as are some causality conditions that belong outside the hierarchy. The investigation relies on the following tools:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…In order to obtain a detailed study on existence and multiplicity of connecting geodesics in exact gravitational waves, Ehrlich and Emch introduced in [14] the concept of "first astigmatic conjugate pairs" for the coordinate u (defined for an ODE system in [17,Definition 3.12]). In that reference they concluded: (a) the existence of a unique connecting geodesic (which is causal for causally related points) whenever u 1 appears before the first astigmatic conjugate point of u 0 , and (b) the non-geodesic connectedness when u 1 is the first astigmatic conjugate point.…”
Section: Conjugate Pointsmentioning
confidence: 99%
“…In order to obtain a detailed study on existence and multiplicity of connecting geodesics in exact gravitational waves, Ehrlich and Emch introduced in [14] the concept of "first astigmatic conjugate pairs" for the coordinate u (defined for an ODE system in [17,Definition 3.12]). In that reference they concluded: (a) the existence of a unique connecting geodesic (which is causal for causally related points) whenever u 1 appears before the first astigmatic conjugate point of u 0 , and (b) the non-geodesic connectedness when u 1 is the first astigmatic conjugate point.…”
Section: Conjugate Pointsmentioning
confidence: 99%
“…As a matter of fact similar examples already appeared in the literature. In fact, after the discovery by Penrose [42] that pp-waves are not globally hyperbolic Ehrlich and Emch [14] showed that they are not even causally simple (for them a ab = δ ab , a, b = 1, 2, b t = 0 and U is a suitable time dependent quadratic form in q 1 and q 2 ). In their study of the general plane waves [17,18] Flores and Sánchez prove (using only differential geometric tools) that if a t is independent of time, (S, a) is a complete Riemannian manifold, b t = 0, and U has a subquadratic behavior at spatial infinity then, (a) the spacetime (M, g) is globally hyperbolic [17,Theor.…”
Section: The Bolza Problemmentioning
confidence: 99%
“…Notice that every metric tensor of the form (21) admits the homothetic vector field ξ = 2u∂ u + x∂ x + y∂ y . A metric tensor which have the form (21) with additionally P ≡ 0 and h ≡ 0 is called a plane wave [6,17]. These plane waves are a subclass of the more general class of pp-waves which have the form ds 2 = −2H (v, x, y) dv 2 − 2 du dv + dx 2 + dy 2 (22) with an arbitrary real function H , which does not depend on u (notice that sometimes in the literature the names of the first two coordinates are changed).…”
Section: With a Matrix P A Function H And A Symmetric Matrix Q Whicmentioning
confidence: 99%